Case Report: Pathological complete response achieved with neoadjuvant immunochemotherapy in synchronous multiple gastric adenocarcinoma - Sun, Ya-hui; Ma, Yan; Chen, Liang; Li, Hai-rong; Liang, Xian-Wen; He, Xiong-hui; Zou, Ke-jian (Frontiers in Immunology, 2025)
Synchronous multiple gastric cancers (SMGC) represent a rare clinical entity with no established treatment guidelines. We report a 76-year-old female with two synchronous poorly differentiated adenocarcinomas (dMMR/MSI-H phenotype) in the gastric lesser curvature, clinically staged as cT4bN2M0. Following three cycles of neoadjuvant immunochemotherapy, the patient demonstrated remarkable tumor regression (RECIST 1.1 partial response) and subsequently underwent R0 distal gastrectomy. Histopathological examination confirmed a pathological complete response (ypT0N0, TRG 0).To our knowledge, this represents the first documented case of SMGC achieving pCR with neoadjuvant immunochemotherapy. Our findings suggest that PD-1 inhibition combined with chemotherapy may induce profound tumor regression in SMGC, even in cases with high tumor burden, potentially converting unresectable to resectable disease. This case provides compelling evidence for incorporating immunotherapy in SMGC management and warrants further investigation through clinical trials.